The genus Commelina (Commelinaceae) in Andaman & Nicobar Islands, India with one new species and three new records - Nampy, Santhosh; Joseph, Sheba M.; Manudev, K.m. (Phytotaxa, 2013)
A synopsis of the genus Commelina in Andaman and Nicobar Islands is presented with one new species and three new records. The new species, C. andamanica is remarkable by its trailing habit without a definite base, solitary and terminal, cucullate spathe with a single cincinnus and two smooth seeds within a capsule. Of the seven species of Commelina recorded, C. attenuata, C. clavata and C. longifolia are new to the islands. An identification key to all the species reported from Andaman and Nicobar Islands is also provided.